IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DI SMA ISLAM TERPADU(SMA-IT) BANGKINANG - Suhendri Suhendri; Makhdalena Makhdalena; Rr. Sri Kartikowati (Universitas Riau, 2018)
Character education is aimed to shape people with strong integrity, good conduct,outstanding morale, being dynamic, competitive, science and technology skills oriented as wellas believing in the One Supreme God. The implementation of character education should besupported by all sides including SMA Islam Terpadu Bangkinang, Kampar District. The purposeof this study was to describe the implementation of character education management at SMAIslam Terpadu Bangkinang covering planning process, implementation and evaluation. The studyemployed qualitative method with triangulation. The validity of the data were checked trhoughreliability, transferability, dependability and confirmability. The data were analyzed using flowmodel of Miles and Huberman and the results of the study showed that the planning processcovered (a) planning conducive school condition, (b) designing explicit character educationcurriculum, (c) creating integrated character curriculum, (d) classroom management, and (e)outside-class environmental management. The implementation stage covered (a) theimplementation of character education in the teaching and learning process, (b) theimplementation of character education in extra-curricular activities, and (c) the implementationof character education in daily life. Finally, evaluation stage focused on (a) the collaborationwith the students’ parents, and (b) the strict control towards good conduct.